Pemeliharaan Akidah Islam: Analisis Daripada Sudut Penguatkuasaan Undang-Undang dan Fatwa di Pulau Pinang: Safeguard the Islamic Faith: An Analysis from Law and Fatwa Enforcement in Pulau Pinang - Sulong, Jasni (Afkar: Jurnal Akidah dan Pemikiran Islam, 2016)
Islamic creed is a principal part of faith and devotion to Allah and His prophet pbuh. The solid creed of a Muslim was established based on his faith to the sixth pillar of Iman and vice versa. Nowadays, challenge to the Islamic creed excelerating due to vast social interactions, internet links and information facilities. Indeed, thoughts that against the Islamic creed such as secular, liberal and Shi’ite are spreading among our young generations. Muslims are deviated with fake information by manipulation of certain individuals towards the Islamic source. Therefore, the government has taken pro-active steps and regulated special laws to overcome the problems. The steps were based on preventive mechanism (sad dhara’i) as well as an enforcement appliance through statutory provisions and rulings (fatwa). Hence, the study is at aim to explore aspects of Islamic creed which is tackled by law and fatwa in order to prevent the threats. The scope of study was focusing on Pulau Pinang which consists of Malays, Chinese and Indians whom the number of them almost at average. The study was done qualitatively by gathering data from statutes and fatwa that were analyzed through content analysis. The study found out that the law has been regulated for many years to prevent deviation of teaching in Islamic creed. However, the sluggish was triggered on the enforcement matter especially where there are many mechanisms at the moment that was manipulate by wrongdoers. Therefore, threats for Islamic creed currently become a paramount challenge for Muslim in this country to follow the right path that was underlined by the prophet pbuh.